1997
DOI: 10.1182/blood.v89.9.3097
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Activity of von Willebrand Factor–Cleaving Protease in Chronic Relapsing Thrombotic Thrombocytopenic Purpura

Abstract: In patients with thrombotic thrombocytopenic purpura (TTP), excessive intravascular platelet aggregation has been associated with appearance in plasma of unusually large von Willebrand factor (vWF ) multimers. These extremely adhesive vWF multimers may arise due to deficiency of a “depolymerase” cleaving vWF to smaller molecular forms, either by reducing the interdimeric disulfide bridges or by proteolytic degradation. We studied the activity of a recently described vWF-cleaving protease in four patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
262
0
6

Year Published

1998
1998
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 515 publications
(271 citation statements)
references
References 27 publications
3
262
0
6
Order By: Relevance
“…Persistent protease deficiency also resulted in the transient appearance of UL-VWF multimers in the PP (Fig 2A) as reflected by increased ratios of VWF:CBA/VWF:Ag on d 131, 180 and 269 ( Fig 1A). Whereas Furlan et al (1997) concluded that the ratio of VWF ristocetin cofactor activity to VWF:Ag was apparently not a reliable parameter for documenting the presence of UL-VWF multimers, we suggest that calculation of the VWF:CBA/VWF:Ag ratio may be more suitable for this purpose. Disappearance of the inhibitor and slight protease recovery (10%) were first detectable as late as 9 months after splenectomy ( Fig 1A).…”
Section: Resultsmentioning
confidence: 66%
“…Persistent protease deficiency also resulted in the transient appearance of UL-VWF multimers in the PP (Fig 2A) as reflected by increased ratios of VWF:CBA/VWF:Ag on d 131, 180 and 269 ( Fig 1A). Whereas Furlan et al (1997) concluded that the ratio of VWF ristocetin cofactor activity to VWF:Ag was apparently not a reliable parameter for documenting the presence of UL-VWF multimers, we suggest that calculation of the VWF:CBA/VWF:Ag ratio may be more suitable for this purpose. Disappearance of the inhibitor and slight protease recovery (10%) were first detectable as late as 9 months after splenectomy ( Fig 1A).…”
Section: Resultsmentioning
confidence: 66%
“…Laboratory tests were performed on blood samples taken during the first days of hospitalization and are reported in Table I and Fig 1. Haemoglobin, platelet count, reticulocyte count, LDH and bilirubin were assayed using routine methods. VWF ristocetin co-factor activity (VWF:Rcof), VWF antigen (VWF:Ag), VWF multimer analysis, immunoblotting and collagen binding assays of VWF-cp activity were performed on citrated plasma samples as previously described (Furlan et al, 1997;Gerritsen et al, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Haemolytic± uraemic syndrome (HUS) is a clinically similar disease in which renal dysfunction predominates. Severe deficiency of von Willebrand Factor-cleaving protease (VWF-cp), resulting in the presence of very adhesive unusually large VWF multimers in plasma has been consistently found in patients with TTP, whereas VWF-cp was normal in patients diagnosed with HUS (Furlan et al, 1997;Furlan et al, 1998a, b;Tsai & Lian, 1998). Oleksowicz et al (1999) reported VWF-cp deficiency (< 15%) in patients with metastasizing malignancies, whereas in patients with localized tumours VWF-cp activity was found to be normal (> 88%).…”
mentioning
confidence: 99%
“…A large number of abnormalities in blood parameters and endothelial function have been reported in TTP, but their role in the pathogenesis has remained unclear (Pettitt & Clark, 1994;Moake, 1997;Schriber & Herzig, 1997;Sniecinski & O'Donnell, 1998;Wright et al, 1999;Rock, 2000). Progress has been recently made in the understanding of the pathogenesis of de novo TTP with the demonstration of deficient von Willebrand factor-cleaving protease activity, which may be inherited or caused by an antibody (Furlan et al, 1997;Cines et al, 2000). Such an enzyme defect does not seem to have a role in stem cell transplantation-associated TTP (van der Plas et al, 1999) and endothelial injury is likely to be the primary event (Cohen et al, 1989;Holler et al, 1989;Sarode et al, 1995;Schriber & Herzig, 1997).…”
mentioning
confidence: 99%